A Mixed Methods Study of Barriers to Help-Seeking for Intimate Partner Aggression in the LGBTQIA+ Community - D’Cruz, Chelsea R. (Journal of interpersonal violence, 2025)
People in the LGBTQIA+ community (i.e., lesbian, gay, bisexual, transgender, queer, intersex, asexual, and other gender/sexual minorities) experience greater rates of intimate partner aggression (IPA) than the general population and have fewer help-seeking pathways available. The current research examined the extent to which LGBTQIA+ people’s perceptions of barriers to help-seeking were associated with perceptions of societal heteronormativity—the belief that being cisgender and heterosexual is the norm—and whether the source of support was formal (e.g., police, counselors) versus informal (e.g., friends, family). The current research was conducted in two parts. In the first part of the study (Study 1a), structural equation modeling indicated a significant positive association between perceived societal heteronormativity and self-focused barriers (e.g., feeling too ashamed or guilty to seek help) but not with other-focused barriers (e.g., expecting unfair treatment). Instead, LGBTQIA+ people perceived greater other-focused barriers when considering formal compared to informal sources of support. In the second part of the study (Study 1b), we interviewed 10 LGBTQIA+ people about barriers to help-seeking for IPA. A reflexive thematic analysis identified four themes: (1) Who can hold the status of being a “victim”?; (2) The heightened importance of autonomy; (3) Formal supports need LGBTQIA+ competency; and (4) Judged by the outside in. The themes illustrated unique barriers experienced by LGBTQIA+ people when judging possible harm, choosing whether to seek help, and actual help-seeking. Altogether, current help-seeking pathways for IPA are generally inaccessible to people in the LGBTQIA+ community. IPA interventions for the LGBTQIA+ community require awareness of stigma, improved education for informal and formal support pathways, and the development of community-led interventions.